DESIGN TOOLS RECYCLED PAPER PRESS FOR THE MAKING OF PAPER FROM YOUNG COCONUT FIBER WASTE AND WASTE PAPER FOR HOME INDUSTRY BUSINESS - Enda Apriani (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2019)
Processing of waste paper into recycled products has been carried out. Young coconut fiber and waste paper can be used as recycled paper for the industry. This research was conducted with the aim of designing the design of recycled paper presses to accelerate the drying of paper sheets made by manual processes. The research variable used is the composition of young coconut fiber (SKM) raw materials and used paper (KB) of 25: 75; 50: 50; 75: 25 (%) on variations in the proportion of PVAc adhesive types, namely 2% and 5% respectively. The results of this study produced a recycled paper press tool to dry paper sheets and the most optimal composition in producing paper for industrial needs, namely the composition of SKM: KB raw materials of 25: 75 (%) on the variation of 2% PVAc adhesive.